2022
DOI: 10.1039/d2ra06785d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of CO gas sensing performance by Mn-doped porous ZnSnO3 microspheres

Abstract: Mn site in ZnSnO3 plays a critical role to adsorb CO molecules. This generates more number of oxygen vacancies in the lattice and hence more number of free electrons, improving the gas sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…The {100} facets contain rows of alternative Li/Fe atoms and O atoms, whereas the {111} facets contain only Li/Fe atoms, which favors the adsorption of more oxygen or analyte molecules. When the LiFeO 2 truncated octahedron sensor is exposed to air, the atmospheric oxygen molecules interact with the surface of the material as per eqn and trap free electrons from the conduction band to form surface-adsorbed oxygen ions like O 2 – and O – as per eqs and , resulting in the formation of a depletion layer on the LiFeO 2 truncated octahedron surface as shown in Figure c, which leads to an increase in the base resistance. O 2 ( g a s ) O 2 false( a d s false) O 2 ( a d s ) + e normalO 2 false( normala normald normals false) normalO 2 false( normala normald normals false) + e 2 O false( normala normald normals false) …”
Section: Resultsmentioning
confidence: 99%
“…The {100} facets contain rows of alternative Li/Fe atoms and O atoms, whereas the {111} facets contain only Li/Fe atoms, which favors the adsorption of more oxygen or analyte molecules. When the LiFeO 2 truncated octahedron sensor is exposed to air, the atmospheric oxygen molecules interact with the surface of the material as per eqn and trap free electrons from the conduction band to form surface-adsorbed oxygen ions like O 2 – and O – as per eqs and , resulting in the formation of a depletion layer on the LiFeO 2 truncated octahedron surface as shown in Figure c, which leads to an increase in the base resistance. O 2 ( g a s ) O 2 false( a d s false) O 2 ( a d s ) + e normalO 2 false( normala normald normals false) normalO 2 false( normala normald normals false) + e 2 O false( normala normald normals false) …”
Section: Resultsmentioning
confidence: 99%
“…The reaction processes are apparent in eqn (2)–(5) . 24 O 2 (gas) → O 2 (ads) O 2 (gas) + e − → O 2 − , T < 100 °C O 2 − + e − → 2O − (ads), 100 °C < T < 300 °C O − (ads) + e − → O 2− (ads), T > 300 °C C 2 H 10 O + 12O − → 4CO 2 + 5H 2 O + 12e − e − + h + → null …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that transition metal doping alters the electronic dimensions, provides structural stability, and tunes the light absorption. [14][15][16][17] In most of the previously reported works on the BV dyebased DSSCs, generally photoanode structures were examined to investigate the device performance and stability. Although many nanostructured photoanodes were investigated it was impossible to significantly enhance the DSSC performance due to the insufficient charge collection efficiency, low photoscattering, and higher interfacial charge recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the transition metal doping alters the electronic dimensions, provide structural stability, and tuned the light absorption. [14][15][16][17]…”
mentioning
confidence: 99%